2004
DOI: 10.1203/01.pdr.0000132752.94155.13
|View full text |Cite
|
Sign up to set email alerts
|

Positive End Expiratory Pressure during Resuscitation of Premature Lambs Rapidly Improves Blood Gases without Adversely Affecting Arterial Pressure

Abstract: Positive end expiratory pressure (PEEP) is important for neonatal ventilation but is not considered in guidelines for resuscitation. Our aim was to investigate the effects of PEEP on cardiorespiratory parameters during resuscitation of very premature lambs delivered by hysterotomy at~125 d gestation (term 147 d). Before delivery, they were intubated and lung fluid was drained. Immediately after delivery, they were ventilated with a Dräger Babylog plus ventilator in volume guarantee mode with a tidal volume of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
73
1
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(90 citation statements)
references
References 43 publications
11
73
1
5
Order By: Relevance
“…6 It appears that widespread use of PEEP during neonatal resuscitation is derived from animal models and observational studies. 7,8 In this study, T-piece increased the mean 1-min to 5-min Apgar score more rapidly than SIB. Although a statistically significant difference in rate of rise was seen between the 2 devices, since the Apgar score at 5 min were not found to be different, the conclusion that the T-piece is superior cannot be definitively stated.…”
Section: Discussionsupporting
confidence: 44%
“…6 It appears that widespread use of PEEP during neonatal resuscitation is derived from animal models and observational studies. 7,8 In this study, T-piece increased the mean 1-min to 5-min Apgar score more rapidly than SIB. Although a statistically significant difference in rate of rise was seen between the 2 devices, since the Apgar score at 5 min were not found to be different, the conclusion that the T-piece is superior cannot be definitively stated.…”
Section: Discussionsupporting
confidence: 44%
“…However, a specific PEEP level is not recommended, and the guidelines warn that "high levels" of PEEP (8-12 cmH 2 O) may reduce pulmonary blood flow and increase the risk of pneumothoraces (8,24). These guidelines draw on studies in immature animals in which high V T s at birth were reported to cause lung injury, impair gas exchange, and reduce lung compliance (N.H. Hillman, T.J. Moss, I. Nitsos, A.H. Jobe, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…PPV with a high tidal volume (V T ) causes lung injury (3)(4)(5)(6) as does PPV of poorly aerated lungs (7). Providing positive end-expiratory pressure (PEEP) immediately after birth quickly improves oxygenation (8) and the establishment of an FRC (9). However, the optimal PEEP required during resuscitation of very preterm infants is not known.…”
mentioning
confidence: 99%
“…14,17,22 Others have demonstrated that a properly inflated lung is important in achieving and maintaining proper oxygenation and that infants with inadequate FRC are more prone to desaturation events. [10][11][12][13] Deckardt et al continuously measured SpO 2 of newborns and delivered continuous positive airway pressure to those who failed to achieve an SpO 2 of 80% by 5 min of age. 4 They found that the use of continuous positive airway pressure improved oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…5,9 For infants requiring resuscitation, the mode of oxygen (O 2 ) delivery may be an important factor in affecting oxygenation. [10][11][12][13] Oxygenation is promoted by providing supplemental O 2 and/or establishing functional residual capacity (FRC) using positive pressure. Continuous positive airway pressure is effective at establishing FRC in the newborn and reducing ventilationperfusion mismatch through recruiting collapsed alveoli and stabilizing alveoli that are already patent, thereby improving oxygenation.…”
Section: Introductionmentioning
confidence: 99%